If it's not what You are looking for type in the equation solver your own equation and let us solve it.
(x+1.5)(x+3)=0
We multiply parentheses ..
(+x^2+3x+1.5x+4.5)=0
We get rid of parentheses
x^2+3x+1.5x+4.5=0
We add all the numbers together, and all the variables
x^2+4.5x+4.5=0
a = 1; b = 4.5; c = +4.5;
Δ = b2-4ac
Δ = 4.52-4·1·4.5
Δ = 2.25
The delta value is higher than zero, so the equation has two solutions
We use following formulas to calculate our solutions:x_{1}=\frac{-b-\sqrt{\Delta}}{2a}x_{2}=\frac{-b+\sqrt{\Delta}}{2a}x_{1}=\frac{-b-\sqrt{\Delta}}{2a}=\frac{-(4.5)-\sqrt{2.25}}{2*1}=\frac{-4.5-\sqrt{2.25}}{2}x_{2}=\frac{-b+\sqrt{\Delta}}{2a}=\frac{-(4.5)+\sqrt{2.25}}{2*1}=\frac{-4.5+\sqrt{2.25}}{2}
| 3n-3=108 | | 2c-3=5-2c | | 2c-3=5-3c | | 9=h/4h= | | g+13=59 | | x=1.5x=3 | | –4−8u=8−5u | | 4-10y-y=-2 | | –4x=69 | | b-40=16 | | 49=x^2+18x+130 | | x÷9=63 | | –10−3b=–5b+10 | | 3a(a-2/3)=3/4a+9/4 | | 1/3(x-20)=2 | | 4(1x-1)+9=17 | | w^2-87=-87 | | g-92=2 | | g^2-32=0 | | u^2=44 | | x×0.2=10 | | k^2+83=0 | | z^2-99=-40 | | x/3/5=1/3 | | x/3/5=1/ | | z/65=13 | | t^2+39=97 | | 36^x=216^-3x+1 | | w+17=70 | | z÷65=13 | | y-3.7=18 | | 3x+4−5(6+2x)=9−3(3x−7) |